Representasi Domestikasi Perempuan dalam Iklan - Siswati, Endah (Jurnal ILMU KOMUNIKASI, 2014)
Abstract: Persuasive strategies in advertisement often use signs or languages representing gender biases in society. These gender biases are especially depicted in the use of woman figure as a sign object, which often shows physical exploitation and woman domestication. However, woman’s role in public area has been developed and advanced in terms of number as well as role and job diversity. Thus, this paper discusses the current tendency of media especially printed ones to represent woman domestication. Also, how advertisement portrays woman domestication in general.Abstrak: Strategi persuasif dalam iklan kerap menggunakan tanda atau bahasa yang menyentuh bias gender dalam masyarakat. Bias gender tersebut utamanya menyangkut penggunaan figur perempuan sebagai objek tanda yang mengeksploitasi tubuh dan daya tarik seksual perempuan. Bias gender tersebut juga sering ditampilkan dalam bentuk subordinasi dan domestikasi perempuan. Di sisi lain, peran perempuan di wilayah publik telah mengalami perkembangan dan kemajuan. Ini bisa dilihat selain dari segi jumlah juga dalam jenis pekerjaan dengan beragam kedudukan di masyarakat. Tulisan ini membahas kecenderungan iklan di media cetak, khususnya, dalam merepresentasikan domestikasi perempuan.